SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SANTRI BARU TERAS TAHFIDZ DI TERAS DAKWAH MENGGUNAKAN METODE TOPSIS - Yuli Praptomo PHS; Selfia Destiana (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2020)
This research was made to build a decision support system application for selecting new prospective students in the Teras Tahfidz. The methodology used in the decision support system process uses the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method. It is hoped that this research can improve the quality of students enrolled later, and can make time efficient in selecting students. By using the Topsis Method, in this study a case will be raised, namely finding the best alternative based on predetermined criteria using the Topsis method. This method was chosen because it is able to select the best alternative. A number of alternatives, in this case the intended alternatives are new students of Teras Tahfidz who register based on specified criteria. The study was conducted by finding the value of the level of importance for each attribute, then carried out the process.